Post-Surgical Rehabilitation and Outcomes in Orthopaedic Patients: A Comprehensive Review of Weight-Bearing and Non-Weight-Bearing Protocols. - Dr. Hassanien Al-Hashimi, Mr. Mohammed Al-Maiyah, Dr. Rand Khalid, Dr. Ayat Mahmood Shakir, Ali HatfAl-Zeregawe, Hebatalrahman Hussein Falih, Hayder Hazim Abdulsada (South Eastern European Journal of Public Health, 2025)
Orthopaedic surgeries comprise of joint replacements, fracture fixations among other procedures that aim at enhancing the patients’ movement and quality of life. However, it is a well known fact that the appropriate post-surgical rehabilitation plays a pivotal role in the recovery process. This review aims to assess the weight bearing (WB) and non weight bearing (NWB) protocols in orthopaedic patients, the consequences of such protocols on recovery, functional results and costs. We reviewed 50 studies and found that early mobilisation is associated with a number of benefits while at the same time carrying certain risks including those related to muscle disuse; we also explore such issues as the use of combined protocols and the role of assistive technologies. The review also focuses on the rehabilitation using the patient-centered approach and recommending the individualised protocols depending on the patient’s requirements and surgical procedures.